Revisions in the Norwegian National Accounts: Accuracy, unbiasedness and efficiency in preliminary figures - Magnus Kvåle Helliesen; Håvard Hungnes; Terje Skjerpen (Statistics Norway, Research Department, 2020)
This paper investigates the quality of preliminary figures in the Norwegian national accounts. To address the problem of few observations in such analyses, we use some recently developed system tests. Preliminary figures for gross fixed capital formation (investments) under-predict the final figures. For other series in the Norwegian national accounts, we find that they are unbiased and weakly efficient.
Keywords: C12; C22; C32; E01; 330; Forecasting